Global value chains (GVCS) in East Asia during the COVID-19 pandemic – the perspective of Japan - Bobowski, Sebastian; Drelich-Skulska, Bogusława (Globalne łańcuchy wartości (GŁW) w Azji Wschodniej w dobie pandemii COVID-19 – perspektywa Japonii, 2022)
GVCs have become an inherent component of the economic landscape of East Asia, one of the key pillars of the regional integration processes and division of labour based on fragmentation and specialisation. The main objective of the paper was to describe the impact of COVID-19 pandemic on GVCs in East Asia from the perspective of Japan, using monthly trade statistics for 2020-2021. The paper indicates the short-term disruptive impact on trade statistics with the prospect of improvement, however, under conditions of the gradual phasing out of the pandemic, the effective utilisation of RCEP concessions to boost GVC trade, and with the better coordination of the regional response to future health crises. Statistical analysis is accompanied by critical analysis of literature in the field of research. The paper delivers the current statistical picture of the impact of the COVID-19 pandemic on intra-RCEP trade, accompanied by references to legal and institutional aspects of the response of individual countries to health crisis.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2022; vol. 66, nr 1, s. 1-13
Keywords: global value chains; COVID-19; pandemic; Japan; globalne łańcuchy dostaw; pandemia COVID-19; Japonia